Potential of Fruit Peels in Becoming Natural Coagulant for Water Treatment - Zaidi, Nur Syamimi (International Journal of Integrated Engineering, 2019)
The effectiveness of chemicals as coagulants such as alum and ferric chloride is well recognized. However, there are many disadvantages associated with the usage such as high operational costs, detrimental effects on human health, production of large sludge volumes and the fact that it is significantly affect pH of treated water. It is therefore desirable to replace these chemical coagulants with natural-based coagulants such as from fruit peels to counteract the aforementioned drawbacks. Therefore, the aim of this study is to investigate the efficiency of fruits peels as natural coagulants in treating water over the use of alum. In terms of selection of natural coagulants, this study focused on the local waste materials, which are banana peels, orange peels and mango peels. These peels were collected from neighborhood and local stall and market. These peels were prepared by washing, drying, grinding and finally sieving, thus becoming powder of natural coagulants ready to be used. A series of jar test was then performed to determine the effect of individual natural coagulants on the efficiency of turbidity removal and coagulation activity under various operating factors such as type and concentration of solvents, pH and coagulant dosage. From the findings, optimum solvent concentration of 2.0M of sodium hydroxide (NaOH) reacted with mango peels at optimum pH and coagulant dosage of pH 2 and 110 mg/L, respectively showed greatest turbidity removal of 92.7% compared to the other tested natural coagulants including chemical coagulant, which was alum. Therefore, it can be concluded that the natural coagulant in specific mango peels pose a great potential in replacing chemical coagulant for the treatment of water.